2014
DOI: 10.1038/ncomms6203
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes stem cell phenotypes and poor prognosis through epigenetic regulation of DICER

Abstract: MicroRNAs are small regulatory RNAs that post-transcriptionally control gene expression. Reduced expression of DICER, the enzyme involved in microRNA processing, is frequently observed in cancer and is associated with poor clinical outcome in various malignancies. Yet the underlying mechanisms are not well understood. Here, we identify tumor hypoxia as a regulator of DICER expression in large cohorts of breast cancer patients. We show that DICER expression is suppressed by hypoxia through an epigenetic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(159 citation statements)
references
References 71 publications
(102 reference statements)
5
149
2
Order By: Relevance
“…Choi et al (36) reported that Kdm6a represses EMT genes and inhibits EMTinduced cancer stemness properties in breast cancer. Similarly, van den Beucken et al (37) showed that hypoxia inhibits KDM6A and induces the hypermethylation of DICER, leading to the up-regulation of ZEB1 expression and promotion of EMT and cancer stemness. In contrast, Thieme et al (58) showed that Kdm6a positively regulates the migration of hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al (36) reported that Kdm6a represses EMT genes and inhibits EMTinduced cancer stemness properties in breast cancer. Similarly, van den Beucken et al (37) showed that hypoxia inhibits KDM6A and induces the hypermethylation of DICER, leading to the up-regulation of ZEB1 expression and promotion of EMT and cancer stemness. In contrast, Thieme et al (58) showed that Kdm6a positively regulates the migration of hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is also an inducer of EMT (32). Seven of the 23 trunk drivers are known human cancer genes, whereas five-Met, Lpp, Pbx1, lysine-specific demethylase 6A (Kdm6a), and Nf1-are reportedly involved in regulating EMT (32)(33)(34)(35)(36)(37). Another trunk driver, Rasa1, is a Ras GTPase-activating protein that suppresses oncogenic Ras signaling, another EMT inducer (5).…”
Section: Identification Of Ccgs Driving the Development Of Mesenchymalmentioning
confidence: 99%
“…Targeting processes involved in epigenetic regulation of gene expression has also been investigated. Inhibition of the H3 K27me3 demethylases KDM6 A/B by GSKÀJ4 was shown to promote EMT in MCF-7 and HMLER cells, [74] suggesting that targeting epigenetic modifiers could provide the means to alter EMT for therapeutic purposes. Diallyl trisulfide (DAST) targets FOXQ1, [75] a protein implicated in embryonic development, cell cycle regulation, tissue-specific gene expression, cell signaling, and tumorigenesis in MCF-7 and SUM159 cells.…”
Section: Miscellaneousmentioning
confidence: 99%
“…For example, the formation of heterochromatin requires Dicer expression. 40,41 Additionally, siRNA mediated knockdown of Dicer induced histone acetylation and promoted heterochromatin switching to euchromatin. 40 Hypoxia, through the inhibition of H3K27me3 demethylases KDM6A/B, was able to epigenetically silence the DICER promoter and reduce Dicer expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%